Youth and jobs in rural Africa: Beyond stylized facts - Mueller, Valerie; Thurlow, James (International Food Policy Research Institute, 2019)
Sub-Saharan Africa's rural population is growing rapidly, and more young people are entering the labour market every year. This raises serious policy questions. Can rural economies absorb enough job seekers? Could better-educated youth transform Africa's rural economies by adopting new technologies and starting businesses? Are policymakers responding to the youth employment challenge? Or will there be widespread unemployment, social instability, and an exodus to cities and abroad? Youth and Jobs in Rural Africa: Beyond Stylized Facts uses survey data to build a nuanced understanding of the constraints and opportunities facing rural youth in Africa. Addressing the questions of Africa's rural youth is currently hampered by major gaps in our knowledge and stylized facts from cross-country trends or studies that do not focus on the core issues. Youth and Jobs in Rural Africa takes a different approach, drawing on household and firm surveys from selected African countries with an explicit focus on rural youth. It argues that a balance between alarm and optimism is warranted, and that Africa's "youth bulge" is not an unprecedented challenge. Jobs in rural areas are limited, but agriculture is transforming and youth are participating, adopting new technologies and running businesses. Governments have adopted youth employment as a priority, but policies often do not address the specific needs of rural populations. Youth and Jobs in Rural Africa emphasizes that by going beyond stylized facts and drawing on more granular analysis, we can design effective policies to turn Africa's youth problem into an opportunity for rural transformation.